2021
DOI: 10.1155/2021/5985377
|View full text |Cite
|
Sign up to set email alerts
|

Marine Macroalgae Display Bioreductant Efficacy for Fabricating Metallic Nanoparticles: Intra/Extracellular Mechanism and Potential Biomedical Applications

Abstract: The application of hazardous chemicals during nanoparticle (NP) synthesis has raised alarming concerns pertaining to their biocompatibility and equally to the environmental harmlessness. In the recent decade, nanotechnological research has made a gigantic shift in order to include the natural resources to produce biogenic NPs. Within this approach, researchers have utilized marine resources such as macroalgae and microalgae, land plants, bacteria, fungi, yeast, actinomycetes, and viruses to synthesize NPs. Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 255 publications
(282 reference statements)
0
16
0
Order By: Relevance
“…32 Macroalgae, referred to as seaweeds, are multicellular, structurally complex and can be counted with the naked eye (sizes of up to 60 m in length), while a microscope is needed to observe microalgae (measuring about 3-20 mm), which are single-celled (unicellular) or form single colonies and may be prokaryotic or eukaryotic types. 33,34 Although both algae can be harvested several times in the same year, microalgae are easy to handle and cultivate, grow fast, and are rich sources of nutrients, biomolecules, and bioactive compounds. 34 Live and dead dry microalgae-based biomass may be used for the biosynthesis of NPs.…”
Section: Microalgae As a Raw Materials For The Green Synthesis Of Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Macroalgae, referred to as seaweeds, are multicellular, structurally complex and can be counted with the naked eye (sizes of up to 60 m in length), while a microscope is needed to observe microalgae (measuring about 3-20 mm), which are single-celled (unicellular) or form single colonies and may be prokaryotic or eukaryotic types. 33,34 Although both algae can be harvested several times in the same year, microalgae are easy to handle and cultivate, grow fast, and are rich sources of nutrients, biomolecules, and bioactive compounds. 34 Live and dead dry microalgae-based biomass may be used for the biosynthesis of NPs.…”
Section: Microalgae As a Raw Materials For The Green Synthesis Of Npsmentioning
confidence: 99%
“…Thus, -NH 2 groups play a protective role by coating the NPs, providing stabilization, and preventing agglomeration in intracellular and extracellular processes. 33,48,49 Using Fourier transform infrared spectroscopy (FTIR), Arya A. et al (2020) 50 compared and identified the main functional groups present in an algal extract from B. braunii that could reduce and stabilize palladium and platinum NPs, and revealed the role of protein amides as a capping agent. As another example, Mahajan A. et al (2019) 51 demonstrated the ability of the aqueous extract of C. vulgaris to reduce silver ions in AgNPs, which was also accompanied by its subsequent stabilization.…”
Section: Mechanisms Of the Biosynthesis Of Nps Using Microalgaementioning
confidence: 99%
“…Despite the excellent antibacterial and anti-cancer efficacy of green-synthesized Ag and AuNPs, the mechanism regarding algal metal NPs remains unclear. Furthermore, extensive studies must be conducted to determine the role of specific biomolecules in the production of metal NPs mediated by algae [100] .…”
Section: Unclear Specific Mechanismsmentioning
confidence: 99%
“…Nanoparticles have a wide range of applications, including the medicinal, diagnostic, drug discovery, biological sensor, and reagent industries [ 28 ]. These biologically active nanoparticles are produced by employing various biological fluids as reducing agents for metal and non-metal ions, such as gold, silver, copper, zinc oxide, platinum, and titanium oxide [ 29 ]. The diverse therapeutic applications of nanoparticles, as well as the outbreak of several infectious diseases, motivate this research [ 30 ].…”
Section: Green Synthesis Of Nanoparticles (Nps) For Its Application I...mentioning
confidence: 99%
“…Fungi, bacteria, plants, and algae from the marine have been found to produce nanoparticles [ 12 ]. Green synthetic nanoparticles can be easily decomposed using enzymes included in the nanoparticles, making them more environmentally benign than conventional agents [ 29 ]. The reduction of metal ions by reducing agents found in the organism is essential for the synthesis of metal nanoparticles [ 32 ].…”
Section: Green Synthesis Of Nanoparticles (Nps) For Its Application I...mentioning
confidence: 99%